Sensor location for travel time estimation based on the user equilibrium principle: Application of linear equations - Cao, Shuhan; Shao, Hu; Shao, Feng (Zielona Góra: Uniwersytet Zielonogórski)
Travel time is a fundamental measure in any transportation system. With the development of technology, travel time can be automatically collected by a variety of advanced sensors. However, limited by objective conditions, it is difficult for any sensor system to cover the whole transportation network in real time. In order to estimate the travel time of the whole transportation network, this paper gives a system of linear equations which is constructed by the user equilibrium (UE) principle and observed data.
Keywords: travel time estimation; sensor location; user equilibrium principle; linear equations